Migration and transformation mechanism of nitrogen in the biomass–biochar–plant transport process. (April 2018) - Yuan, Shengnan; Tan, Zhongxin; Huang, Qiaoyun
Abstract: In this paper, we reviewed several biochar studies to systematically examine the complete transport of nitrogen from biomass to biochar to plants. The results can be summarised as follows. (1) Nitrogen from biomass to biochar: the pyrolysis temperature of high-quality biochar for soil improvement is approximately 400 °C, the best preparation atmosphere is CO2, and the retention rate of nitrogen in biochar is greater than 64.94%. More than 70% of the nitrogen in straw exists in the form of proteins, while the remainder is in the form of alkaloid-N, free amine-N, and inorganic NH4 + -N. When biochar is prepared from straw, the organic nitrogen species are pyrrole-N (43.75%), pyridine-N (22.69%), amino-N (11.25%), and nitrile-N (7.48%). In addition, inorganic nitrogen is present as NH4 + -N (14.82%). (2) Nitrogen from biochar to soil: there are two main functions of biochar applied to soil. First, biochar reduces nitrogen leaching from the soil. Second, biochar increases the soil nitrogen content linearly with the amount of biochar applied ( R 2 = 0.9767). (3) Nitrogen from biochar to crops: biochars prepared from straw under different pyrolysis conditions were applied to soil, and crops were cultivated. We found that crops grew best in soil treated with biochar prepared at 400 °C under CO2 atmosphere. The effect of adding straw biochar to the soil is significantly better than the direct addition of plant matter (straw). This paper focuses on the systematic study of the complete nitrogen cycle; that is, nitrogen is taken from plants and then returned to plants. In this way, this study can not only help make full use of biochar to improve soil fertility but also has great significance for biomass energy utilisation, especially for the divided utilisation of biomass energy elements (C and H) and nutrient elements (N and S).